Preparação de ésteres nitrocinâmicos e avaliação da sua atividade antimicrobiana - Nascimento, Lázaro Gomes do (2017)
The present work aimed to prepare a series of esters derived from trans-2-nitrocinnamic acid, through Fischer esterification, nucleophilic substitution with halides and Mitsunobu reaction. All the derivatives were submitted to antimicrobial tests by the microdilution method in broth, and the antimicrobials chloramphenicol and nystatin as positive controls. This study resulted in the obtaining of 14 esters of trans-2-nitrocinnamic acid in yields ranging from 25 to 98%, nine of which were unpublished in the literature, and characterized by infrared spec-troscopic methods, 1H and 13C magnetic resonance, as well as High resolution mass spectrometry. The results of the antimicrobial evaluation showed that ten esters presented antifungal activity against Candida species. While two derivatives were bioactive in the an-tibacterial test. Of these, the EL4, EL6 and EL14 esters were the derivatives that obtained the most promising antifungal minimum inhibitory concentrations with MIC ranging from 128 to 256 μg / mL and considered to be strong activities. Regarding the bacterial activity, EL12 and EL13 derivatives showed activity on the Pseudomonas aeruginosa species with MIC 512 μg / mL. These results demonstrate that the increase of the alkyl chain in the substituent up to a certain size and the presence of hydroxyl, methoxy, or chlorine at the para position of the aromatic ring influence the antifungal activity of the 2-nitrocinnamic esters.